2003
DOI: 10.1046/j.1365-2265.2003.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol regulates the expression of the genes encoding the three key vitamin D3 hydroxylases and the drug‐metabolizing enzyme CYP3A4 in the human fetal intestine

Abstract: Collectively, the data illustrate that at mid-gestation 1,25(OH)2D3 is fully active in the modulation of all D3-hydroxylases in the human developing intestine. They also show that the detoxifying enzyme CYP3A4 is not only present along the intestinal tract but is also sensitive to 1,25(OH)2D3, indicating that the hormone may be a key element in intestinal development and in the maintenance of the intestinal mucosa integrity in the basal state and in response to damage-inducing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 53 publications
(51 reference statements)
4
43
0
Order By: Relevance
“…In contrast, 1α,25(OH) 2 D 3 was a weak inducer of CYP3A4 compared with rifampicin or the other PXR activators but appeared as the most potent inducer of the CYP24 gene. As previously observed in other tissues (34), 1α,25(OH) 2 D 3 produced a significant decrease (50% inhibition, P < 0.01) of the CYP27B1 mRNA level (Figure 1). In contrast, rifampicin, hyperforin, or phenobarbital did not affect the expression of this mRNA.…”
Section: Figuresupporting
confidence: 69%
“…In contrast, 1α,25(OH) 2 D 3 was a weak inducer of CYP3A4 compared with rifampicin or the other PXR activators but appeared as the most potent inducer of the CYP24 gene. As previously observed in other tissues (34), 1α,25(OH) 2 D 3 produced a significant decrease (50% inhibition, P < 0.01) of the CYP27B1 mRNA level (Figure 1). In contrast, rifampicin, hyperforin, or phenobarbital did not affect the expression of this mRNA.…”
Section: Figuresupporting
confidence: 69%
“…B and D: means Ϯ SE of CYP27A-to-18S mRNA ratio assessed by densitometric scanning; n ϭ 4-5 animals/group for studies on gender differences (B); n ϭ 3 animals/group for studies on cytochrome P-450 inducers (D). Statistically significant differences were evaluated by Student's t-test: *P Ͻ 0.05, **P Ͻ 0.0003. metabolize D 3 to 25OHD 3 , as has been clearly illustrated in previous studies on the rat duodenum and human fetal jejunum and colon (59,60).…”
Section: Discussionsupporting
confidence: 48%
“…Although hepatocytes were found to harbor the highest level of the transcript, the observation indicates that cell populations other than hepatocytes may also be involved in the production of 25OHD 3 in the normal rodent liver. These data indicate that CYP27A is more widely distributed than originally thought, as the intestine, kidney, calvaria, long bones, lung, spleen, adrenals, epidermis, and central nervous system have also been shown to express the CYP27A gene transcript (14,36,55,59,60). Circulating macrophages and vascular endothelial cells are also known to harbor the CYP27A gene product and to hydroxylate cholesterol at C-25 as a means of excreting cholesterol (14).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we investigated the applicability of human intestinal precision-cut slices to study induction of DMEs (phase I and II) and DTs up to 24 h of incubation. Theodoropoulos et al showed the inducibility of CYP3A4 in human fetal intestinal biopsies after incubation with calcitriol (Theodoropoulos et al, 2003), but to our knowledge, the present study is the first to test and prove the applicability of human, intact, nonfetal, intestinal tissue for induction studies. We first tested both the viability of the preparations and the stability of the metabolic rates in colon and proximal jejunum slices during 24-h incubations by measuring intracellular ATP levels, examining morphology, and determining stability of the metabolic rate using several substrates: testosterone (TT), substrate for CYP3A4, CYP2B6, and 17␤-HSD (Farthing et al, 1981;Yamazaki and Shimada, 1997);7-ethoxycoumarin (7EC), substrate for CYP1A1, CYP1A2, CYP2B6, and CYP2E1 (Shimada et al, 1999); 7-hydroxycoumarin (7HC), substrate for UGT1A6 and sulfotransferase; and midazolam, coumarin, diclofenac, and bufuralol, substrates for CYP3A4/5, CYP2A6, CYP2C9, and CYP2D6, respectively (Bjornsson et al, 2003).…”
mentioning
confidence: 96%